Effects of cattle grazing crop residues on soil bulk density - Taylor, R.K.; Slocombe, John W. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Effects of cattle grazing on soil bulk density were measured at two sites in central Kansas. Samples were taken at depths of 0 to 3 in. and 3 to 6 in. from grazed and ungrazed areas at five locations in each field. No statistical difference (P>0.01) between bulk densities of the two areas occurred at the 3 to 6 in. depth for either site. However, soil in the grazed areas had significantly higher (P<0.01) bulk density than that in the ungrazed areas at the 0 to 3 in. depth at both sites.
Keywords: Beef; Soil compaction; Stocker cattle; Grazing; Forage